Pattern and determinants of obesity among adolescent females in private and public schools in Olorunda local government area of Osun state, Nigeria: a comparative study - Ebenezer Olubanji Ojofeitimi; Adenike Iyanuoluwa Olugbenga-Bello; Daniel Adebode Adekanle; Adeleye A. Adeomi (AOSIS, 2011)
The prevalence of obesity has continued to rise at an alarming rate world-wide to such an extent that it has been described as a global epidemic. This study aims to determine the pattern and determinants of obesity among adolescent females in private and public schools in Olorunda Local Government Area of Osun state, Nigeria. This is a cross sectional descriptive study. Using the multi-stage sampling technique, 520 pre-tested semi-structured questionnaires were administered to 257 girls from the private schools and 263 girls from the public schools. Most of the respondents from private schools (65.2%) had good knowledge about obesity and related matters, while most from the public schools (65.9%) had poor knowledge. The dietary practice of majority of the girls from private schools (60.2%) was unhealthy, while most of the girls from public schools (68.7%) had healthy dietary practices. Most of the respondents from private schools (64.2%) lived sedentary lifestyles while most from the public schools (64.0%) lived active lifestyles. Using the BMI, majority of the girls from private schools were underweight (52%), 10 (4.0%) were overweight and 3 (1.2%) were obese. For the public schools, using the BMI, majority (55.4%) fell within the normal group, 6(2.3%) were overweight and none was obese. The prevalence of overweight and obesity was higher among the girls in private schools than among girls attending public schools. Awareness should be created to promote a healthy balance of food, drink and physical activity within and outside the school.